幼兒教育階段核心素養之研究A Study of the Key Competencies of Early Childhood Education - 盧美貴Mei-Gui Lu; 黃月美Yueh-Mei Huang; 陳玉芳Yu-Fang Chen (Higher Education Foundation, 2013)
本研究主要是探討臺灣幼兒教育階段核心素養的內涵，透過文獻分析、各國核心素養之比較、德懷術問卷調查、小組會議及領域專長學者審查會議，本研究獲得幾項重要的結論：一、臺灣對於幼兒的期待與幼兒核心素養深受華人文化脈絡之影響；二、幼兒核心素養包含三個層面，分別是「溝通互動」、「社會參與」及「自主行動」；三、幼兒教育階段課程之基本理念應在華人文化脈絡下，涵蓋幼兒核心素養之態度與能力，以幼兒為主體之探索、覺察、理解與欣賞的歷程。最後，本研究根據研究結果提出諸多建議，做為幼兒課程政策擬定以及後續研究之參酌。The aims of this study was to explore the key competencies of early childhood education in Taiwan, and to analyze how it can improve curriculum. Through literature review, the comparison of key competencies among different countries, Delphi technique, group meetings and review seminar of subject specialists curriculum specialty, the research got a few important conclusions. First, the expectation considering about children's key competencies is deeply influenced by the Chinese parenting approaches. Secondly, children's key competencies in Taiwan in the research include three dimensions: communicative interaction, social participation, and autonomous action. The research also presented the basic ideas of early childhood curriculum which are the process about taking children whose attitude and ability are cultivated under the Chinese cultural context as the subject of exploration, awareness, understanding and appreciation. In addition to understand early childhood education courses and other stages of phase coherence, the results of this research made many recommendations for policy formulation about early childhood curriculum, and subsequent researchers for reference.